Peran Kepala Madrasah dalam Menumbuhkan Budaya Evaluatif di Kalangan Guru Madrasah Aliyah di MAS Al-Washliyah 22 Tembung - Syaripatussuriyani Hasibuan; Mesiono (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the evaluative culture among teachers at the Al-Washliyah 22 Tembung Private Islamic Senior High School (MAS) and describe the role of the principal in building an evaluative culture in learning. The study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The research subjects consisted of the principal, vice principal, and teachers. The results showed that the evaluative culture at MAS Al-Washliyah 22 Tembung has been implemented through academic supervision, evaluation meetings, and regular teacher coaching. The principal acts as a leader, mentor, motivator, and supervisor in supporting the implementation of learning evaluation. However, several obstacles were still found, such as teachers' understanding that evaluation is only an administrative activity, less than optimal follow-up of evaluation results, and low innovation in the implementation of learning evaluation. This study concludes that the success of an evaluative culture is not only influenced by the principal's policies, but also by teachers' awareness and commitment in making evaluation part of improving learning professionalism.